REIMAGINING CHARACTER EDUCATION: INNOVATIONS IN CULTIVATING VALUES AMIDST THE ADVANCEMENTS OF CIVILIZATION - Syadzali, Ahmad Alfi Nur; Asrori, Mohammad; Kawakip, Ahmad Nurul (STIT Ibnu Rusyd Tanah Grogot, 2024)
This study aims to analyze the integration of character values ​​in the learning process at SD Negeri 2 Jatipunggur and its contribution to the formation of student character. This study is based on the importance of character education as an effort to produce students who are not only academically superior but also have strong morality and integrity. Character education in this school focuses on values ​​such as honesty, responsibility, discipline, cooperation, and tolerance, which are integrated into the curriculum, extracurricular activities, and through the role models of teachers and school staff. The study used a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation. Data analysis techniques refer to the interactive model of Miles and Huberman, which involves data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integration of character values ​​is carried out through collaborative and participatory learning that encourages students to be active, work together, and support each other. Extracurricular activities such as scouts, sports, and arts also strengthen the formation of student character. In addition, teachers and staff act as role models who provide real examples of behavior that reflect these values. These findings are expected to be a reference for the development of character education programs in other schools with similar contexts.